2021
DOI: 10.3389/fpubh.2020.627472
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Work Engagement, Psychosocial Risks, and Mental Health Among Spanish Nurses: A Cross-Sectional Study

Abstract: Background: Exposure to risk factors may lead to health problems of varied nature and to an increased risk of suffering accidents at work.Objectives: The aim of this study was to evaluate the work engagement, psychosocial risks, and psychological well-being of Spanish nurses, analyzing existing relationships, and their associations with self-reported mental health problems of nurses.Methods: To this end, a cross-sectional observational study was carried out with a sample of 1,704 Spanish nurses between January… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
20
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 34 publications
(55 reference statements)
6
20
1
2
Order By: Relevance
“…However, many studies on nurses from other countries have reported mean engagement scores above 4 out of 6 in all three dimensions [58][59][60]. For example, a study from 185,835 Spanish nurses reported a mean engagement score of 4.59 [61]. Nevertheless, the work engagement scores tended to have positive correlations with nurses' age in the current study, which is consistent with findings from other studies [62][63][64].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, many studies on nurses from other countries have reported mean engagement scores above 4 out of 6 in all three dimensions [58][59][60]. For example, a study from 185,835 Spanish nurses reported a mean engagement score of 4.59 [61]. Nevertheless, the work engagement scores tended to have positive correlations with nurses' age in the current study, which is consistent with findings from other studies [62][63][64].…”
Section: Discussionsupporting
confidence: 90%
“…Nurses working in LTC facilities had relatively poor work engagement levels. The mean work engagement score of nurses in LTC facilities was compared with data from previous studies to elucidate the characteristics of the study sample [57][58][59][60][61]. The mean work engagement scores in this survey were 2.98, and nurses working in LTC facilities appeared to be less engaged in their work than other occupations in Japan.…”
Section: Discussionmentioning
confidence: 96%
“…25 Mitonga-Monga and Hlongwane explained this relationship by arguing that workers with a high sense of coherence achieve their work objectives by perceiving the world as predictable, organized, and orderly. 50 A worse state of mental health, as occurs during psychological distress, is associated with a lower WE, as was observed in the study by García-Iglesias et al 51 with Spanish nurses and in papers such as Gorter and Freeman 52 and Holmberg et al 53 with health workers.…”
Section: Discussionmentioning
confidence: 71%
“…However, their “unreal” absence does not indicate well-being at work. The literature shows that commitment and job satisfaction increase the positive bonds of health professionals with the work environment to the extent that job involvement increases when professionals learn to decrease occupational risks, which contributes to greater job involvement and pleasant working hours [ 51 , 52 , 53 , 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%